DIRECT OPEN STRATEGY IN JAVANESE APOLOGY SPEECH ACT: A PRAGMATIC STUDY - Maruti, Endang Sri (ppjbsip, 2021)
This study aims to find forms and explanations of open strategies directly on the speech act of apologizing in Javanese. This study uses a qualitative descriptive approach with an ethnopragmatic design. Research data obtained from 46 research subjects through observation and in-depth interviews. Data analysis was carried out with a flow model in which there were reduction, presentation, verification, and inference. The results showed that direct 'open' strategy are (a) praising the pt first, (b) sympathizing, (c) using group similarity markers, (d) seeking or asking for opinions, (e) making offers and promises, (f ) giving reasons, (g) giving respect, (h) admitting mistakes, (i) begging very much, and (j) repeating an apology